Motivasi Wisatawan Berkunjung ke Agrowisata Malini Agropark sebagai Daya Tarik Wisata di Desa Pecatu Kecamatan Kuta Selatan Kabupaten Badung - SINURAT, REHULINA BR; DIARTA, I KETUT SURYA; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
The Motivation of Tourists Visiting to the Malini Agropark Agrotourism as a Tourist Attraction in Pecatu Village , South Kuta sub-district Badung district Tourists are very influential in the development of tourism to provide products and services in accordance with the interests and needs of visitors is no exception Malini Agropark. One of the determinants of tourists visit attractions is the motivation.This research about the motivation of tourists who encourage and attract tourists to visit the farm Malini Agropark. The goal is to describe the intrinsic and extrinsic motivation of tourists visit Malini Agropark. Respondents of the study were 30 people. Data collection techniques used are questionnaires and interviews. This research uses descriptive qualitative techniques. The results showed intrinsic motivation indicators is the need to take a break and relax yourself and need out of a routine. The scores obtained 886, then intrinsic motivation is very high. Indicators most high in extrinsic motivation is enjoying the view in Malini Agropark and take pictures on the spot a good photo. The scores obtained 1177, extrinsic motivation is categorized high. Based on the results of the study need to be an increase in facilities to support the needs, comfort and satisfaction of tourists when you are in Malini Agropark.